Application Of Artificial Intelligence in Chatbot Application As Palm Oil Price Information System and Capacity On Ramp in Labuhanbatu - Fitri Aini Nasution; Muhammad Halmi Dar (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
This study aims to facilitate palm oil entrepreneurs in obtaining information on palm oil prices using advanced technology, based on research conducted are still using methods that are considered less efficient in providing price information to customers. after this study, palm oil entrepreneurs can easily get information about the price of palm oil in Ramp Nina, Pulo Padang Village. customers will get information on palm oil prices by simply calling the whatsapp number used to provide information on palm oil prices then the chatbot will provide information on palm oil prices to customers. it is considered quite efficient in solving existing problems.